2019
DOI: 10.1002/ajmg.a.61126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical exome sequencing in 509 Middle Eastern families with suspected Mendelian diseases: The Qatari experience

Abstract: BackgroundClinical exome sequencing (CES) is rapidly becoming the diagnostic test of choice in patients with suspected Mendelian diseases especially those that are heterogeneous in etiology and clinical presentation. Reporting large CES series can inform guidelines on best practices for test utilization, and improves accuracy of variant interpretation through clinically‐oriented data sharing.MethodsThis is a retrospective series of 509 probands from Qatar who underwent singleton or trio CES either as a reflex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…The proportion of solved families in our cohort (46.2%) is somewhat higher than the average diagnostic yield in unselected cohorts reported by large clinical diagnostic laboratories, but is in keeping with yields reported in highly consanguineous populations . Our high diagnostic yield likely relates to the intentional focus on consanguineous families, the highly selected nature of our patients based on clinical phenotyping, and the research‐oriented approach to analysis, which resulted in multiple diagnoses in novel genes.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The proportion of solved families in our cohort (46.2%) is somewhat higher than the average diagnostic yield in unselected cohorts reported by large clinical diagnostic laboratories, but is in keeping with yields reported in highly consanguineous populations . Our high diagnostic yield likely relates to the intentional focus on consanguineous families, the highly selected nature of our patients based on clinical phenotyping, and the research‐oriented approach to analysis, which resulted in multiple diagnoses in novel genes.…”
Section: Discussionsupporting
confidence: 70%
“…The diagnostic yield of ES in consanguineous cohorts has been well studied, but much of the published literature has emerged from regions where first and second cousin marriages are routine and consanguinity is common. In such populations, the singleton approach to ES has been used with success reflected in high diagnostic rates . In Canada, consanguinity is not as prevalent, yet the population is extremely heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Biallelic pathogenic variants in one nuclear‐encoded protein, mitochondrial calcium uptake 1 (MICU1) have recently been described to cause myopathy with extrapyramidal signs (MPXPS). MPXPS has been reported in 41 cases (Table S1) and presents with myopathy, learning disability, and extrapyramidal movement disorder . The MICU1 protein regulates calcium influx into mitochondria through interaction with the mitochondrial calcium uniporter (MCU).…”
Section: Introductionmentioning
confidence: 99%
“…Al-Dewik et al, established the genetic diagnosis in 48.3% patients with rare genetic disorders (246/509). Diagnostic yield was higher in consanguineous families (52.4 vs. 39.5%) 19 . Al-Shamsi et al reported 50% ES diagnostic yield among 85 patients suspected to have inborn errors of metabolism 20 .…”
Section: Discussionmentioning
confidence: 87%